The combination of oxaliplatin and anti-PD-1 inhibitor promotes immune cells infiltration and enhances anti-tumor effect of PD-1 blockade in bladder cancer - Zhao, Zihan; Liu, Siyang; Sun, Rui; Zhu, Wenjie; Zhang, Yulin; Liu, Tianyao; Li, Tianhang; Jiang, Ning; Guo, Hongqian; Yang, Rong (Frontiers in Immunology, 2023)
Introduction Bladder cancer (BLCA) is a highly malignant tumor of the urinary system, but the prognosis and survival rates have little improvement based on current therapeutic strategy. Immune checkpoint inhibitors (ICIs) therapy revolutionized the treatment of BLCA, but the clinical application of ICIs is limited by low response rate. Oxaliplatin (OXP), a second line chemotherapy drug for BLCA, may reshape the tumor immune microenvironment (TIME) via recruiting immune cells. Here, we conducted the study of oxaliplatin combined with anti-PD-1 inhibitor in BLCA mice models. Methods The 6-8 weeks old female C57BL/6J mice were used to establish subcutaneous model of bladder tumor. After tumors developed, mice were given tail vein injections of PBS or oxaliplatin (2.5 mg/kg) and/or anti-PD-1 antibody (10 mg/kg). Tumor tissue samples and peripheral blood mononuclear cell (PBMC) were collected to systemically evaluate the efficiency and safety of combination OXP and anti-PD-1 inhibitor. The change of immune cells populations and the corresponding phenotypic diversity in TIME and PBMC were analysed by flow cytometry. Results Tumor growth experiments clarified that the combination therapy was more efficient than medication alone. Flow cytometry analysis of tumor samples showed significant differences between untreated and treated mice. Oxaliplatin influences the TIME by increasing immune cells infiltration, including CD3+ T cells, CD4+ T cells, CD8+ T cells, dendritic cells (DC cells) and natural killer cells (NK cells). As for infiltrating cells, oxaliplatin upregulated the expression of CD134 and downregulated TIM-3 of CD4+ T cells, downregulated the PD-L1 expression of DC cells, which contributed to improve the anti-tumor effect and the treatment response of ICIs. Additionally, the evaluation of PBMC found that there were no significant changes in immune cell subsets and phenotypes, which validated the safety of the combination therapy. These results show the therapeutic potential for the combination of OXP and anti-PD-1 inhibitor in BLCA. Conclusion OXP could increase the infiltration of immune cells in TIME to promote the anti-tumor activity of anti-PD-1 inhibitor. The present research provided an appropriate rationale of combination chemotherapy and immunotherapy therapy for BLCA.